Studi Kinerja Keuangan PT ABC Berdasarkan Rasio Solvabilitas dan Profitabilitas Tahun 2020–2024 - Sukma Ayu; Divianto Divianto; Septini Kumalaputri (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to analyze the financial performance of PT ABC for the 2020–2024 period using a solvency and profitability ratio analysis approach. The background of this study is based on the importance of a company's financial health in maintaining competitiveness and business sustainability amidst increasingly competitive market dynamics. Financial performance analysis not only serves to assess the effectiveness of company resource management but also serves as a reference for investors, creditors, and other stakeholders in making economic decisions. The research method used is quantitative descriptive analysis utilizing secondary data in the form of the company's annual financial reports accessed through the official website of the Indonesia Stock Exchange (IDX). Data collection techniques were carried out through documentation studies, with financial reports for the 2020–2024 period selected using a purposive sampling method. The analysis focused on calculating and interpreting solvency and profitability ratios. The results show that in terms of solvency, the debt to asset ratio (DAR) and debt to equity ratio (DER) tend to be high, reflecting the company's dependence on debt-based financing. This situation can pose financial risks if not balanced with an appropriate debt management strategy, resulting in suboptimal solvency performance. Meanwhile, profitability analysis shows that gross profit margin (GPM), net profit margin (NPM), and return on assets (ROA) are at relatively low levels. This indicates that the company's efficiency in generating profits from sales and asset utilization is not optimal. However, the return on equity (ROE) ratio actually shows quite good performance. This condition indicates that the company is able to optimize shareholder equity to generate a reasonable profit.